2010
DOI: 10.1243/13506501jet740
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and tribological properties of composite FeCrBSi/FeS layer

Abstract: Solid lubrication composite FeCrBSi/FeS layer was prepared by compound technology -combining supersonic velocity plasma spray with low-temperature ion sulphurizing. X-ray diffraction pattern for the composite layer implied that the layer mainly consists of α-Fe and FeS. Scanning electron microscopy was used to observe the surface, cross-section, and worn scar morphologies of the FeCrBSi/FeS layer. The nano-hardness and elastic modulus of the layer were surveyed by a nano-indentation tester. The sliding tribolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The lubricating property of the MoS 2 should be probably attributed to the hardness of the synthetic MoS 2 film, which is higher than that of the FeS film. In addition, the FeS film is porous [10][11], which accelerates the wear process due to a severe stress concentration at pore edges. MoS 2 possesses close-packed hexagonal structure, it can easily slip along the close-packed plane, which attributes to its low friction coefficient.…”
Section: Resultsmentioning
confidence: 99%
“…The lubricating property of the MoS 2 should be probably attributed to the hardness of the synthetic MoS 2 film, which is higher than that of the FeS film. In addition, the FeS film is porous [10][11], which accelerates the wear process due to a severe stress concentration at pore edges. MoS 2 possesses close-packed hexagonal structure, it can easily slip along the close-packed plane, which attributes to its low friction coefficient.…”
Section: Resultsmentioning
confidence: 99%
“…The Ni-and Co-based self-fluxing alloys have very good overall properties but their main disadvantage is the high cost. If the properties of Fe-based alloys were enhanced, the Ni-based self fluxing alloys would be replaced by Fe-based alloys which have a high wear resistance and are relatively cheap [11,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the FeCrBSi/FeS composite layer exhibited frictionreducing effects and an obvious wear resistance in different lubricant conditions in comparison with 1045 steel. Fe-based self-fluxing alloys have a good corrosion resistance and make it possible to obtain a multiphase structure combining a finely dispersed eutectic with a low hardness and an iron borocarbide hard phase, which is the optimum for rubbing pairs operating with high loads and sliding speeds [14].…”
Section: Introductionmentioning
confidence: 99%
“…Comparing with other sulfurizing techniques, low temperature ion sulfurizing technique has lots of merits, such as pollution-free, easy preparation, low cost, and good tribological properties. Moreover, the low temperature ion sulfurizing technique has no influence on the original rigidity, shape, precision of workpieces [7][8][9]. Therefore, low temperature ion sulfurizing is used widely in many industrial field including metallurgy, automobile vehicle, textile, pillow, roller, cutter, cylinder bush and piston ring of engine.…”
Section: Introductionmentioning
confidence: 99%